Serum TNF-, sCD8 and sIL-2R levels in childhood tuberculosis - (:unkn) unknown (My University, 1995)
In this study we have determined the serum tumor necrosis factor-alpha (TNF-alpha), soluble CD8 (sCD8) and soluble interleukin-2 receptor (sIL-2R) levels in children with active pulmonary tuberculosis (n = 66) and healthy controls (n = 20). Measurable serum TNF-alpha levels were detected in nine of 86 children (10.5%), all of whom belonged to the group with active disease. Serum sCD8 and sIL-2R determinations revealed a significant difference between the group with active pulmonary tuberculosis and the controls (p < 0.05). Deeper insight into the involvement of cytokines and T cells will provide a better understanding
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Pediatrik İmmünoloji ve Allerji; Medicine; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Internal Medicine Sciences; Child Health and Diseases; Pediatric Immunology and Allergy; Klinik Tıp (MED); Klinik Tıp; TIBBİ BİLİŞİM; TIP, GENEL & DAHİLİ; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICAL INFORMATICS; MEDICINE, GENERAL & INTERNAL; PEDIATRICS; Pediatri; Aile Sağlığı; Temel Bilgi ve Beceriler; Tıbbi Bilişim; Genel Sağlık Meslekleri; Patofizyoloji; Pediatri, Perinatoloji ve Çocuk Sağlığı; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Pediatrics; Family Practice; Fundamentals and Skills; Health Informatics; General Health Professions; Pathophysiology; Pediatrics, Perinatology and Child Health; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine